Causal relationship between International Financial Reporting Standard (IFRS) and Foreign Direct Investment (FDI) : a panel data analysis of ASEAN countries - Yousefinejad, Maryam; Azlina Ahmad,; Fairuz Md. Salleh,; Ruzita Abdul Rahim, (Penerbit Universiti Kebangsaan Malaysia, 2018)
This study investigates the causal relationship between International Financial Reporting Standard (IFRS) adoption and Foreign Direct Investment (FDI) inflows in ASEAN countries during the period of 2001 to 2016. This study applies panel co-integration and causality test to examine the short and long run and causal relationship between variables. IFRS adoption was measured based on dummy variable in Model 1 and level of IFRS compliance in Model 2. Findings of this study confirm the presence of co-integration between variables and the Dynamic Ordinary Least Square (DOLS) estimation analysis reveals positive and significant relationship between IFRS adoption, based on both measures and FDI inflows. Furthermore, the causality test shows that there is short run causality from IFRS to FDI inflows and long run causality between variables. This study extends knowledge on the relationship between IFRS adoption and FDI inflows by examining this relationship in the setting of ASEAN countries. Findings of this study could be useful for countries which are IFRS adopter and also non-adopters to understand the economic consequences of IFRS adoption, in their effort to attract more investors so as to accelerate economic growth.